2021
DOI: 10.1002/jbio.202100109
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effects of ultrasound and laser therapies on mesentery for management of obesity and diabetes in rats

Abstract: Nowadays, the mesentery as a new organ was discovered. Mesenteric events may play an important role in the pathophysiology of several diseases. The aim of our study was investigate the synergic effects of ultrasound (US) and laser therapies on mesentery in obese-hyperglycemic rats.The 25 male Wistar rats were randomized into five groups. Obese nondiabetic (OND) group: obese rats without diabetes and no treatment conditions; SHAM group: obese-hyperglycemic rats treated with placebo; US group: obese-hyperglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge this is the first study to provide convincing evidence using a randomized, double‐blind, crossover and sham‐controlled clinical trial, of the beneficial effects and the dose–response and time–response effects of PBMt, combined or not with the use of oral hypoglycemic medication, on the glycemic control in T2DM patients. Previous studies from our group [33, 34, 53] and from others [30–32, 35, 54, 55] have suggested PBMt could improve glycemic control in insulin resistant T2DM in animal models, however clinical studies on humans are only beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first study to provide convincing evidence using a randomized, double‐blind, crossover and sham‐controlled clinical trial, of the beneficial effects and the dose–response and time–response effects of PBMt, combined or not with the use of oral hypoglycemic medication, on the glycemic control in T2DM patients. Previous studies from our group [33, 34, 53] and from others [30–32, 35, 54, 55] have suggested PBMt could improve glycemic control in insulin resistant T2DM in animal models, however clinical studies on humans are only beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%